Spatial analysis of the agricultural sustainability gap based on the TOPSIS-GIS approach - Morad Ebrahimi; Hasan Afrakhteh; Hamid Jalalian (تحقیقات کاربردی علوم جغرافیایی)
Abstract Although decades have passed since the introduction of a sustainable agricultural approach in the country, But the agricultural system is based on the use of non-native technologies, use of chemical inputs and Excessive exploitation of nature and Therefore, the formation and development of sustainable agriculture has faced major challenges. In this research, the researchers, considering the importance of agricultural sustainability especially in rural areas of the country and its role in maintaining the basic resources, considered the issue of agricultural sustainability In the villages of the central district of kuhdasht county and have studied and analyzed the agricultural sustainability gap in this region. For this purpose, 20 villages were selected by stratified random sampling method based on the location of the villages (plain, mountainous, and foothills), indicators of agricultural sustainability were developed and After completing the questionnaires by agricultural users, coding and data entry were performed in Excel and SPSS. Then, using the TOPSIS multivariate decision analysis, the studied villages were classified based on agricultural sustainability and They were classified into four clusters (Stable, semi-stable, unstable and very unstable) using cluster analysis. The results of the study showed that the agricultural sustainability level in the villages of this region is unbalanced in ecological, social and economic dimensions. This imbalance was seen both in the rural districts and at the level of studied villages.